Sustaining learning organization in the next normal of educational management: Evidence from Malaysia - Noraine Jamil; Mohd Izham Mohd Hamzah; Aida Hanim A. Hamid (International Journal of Evaluation and Research in Education (IJERE), 2023)
Organizations experience severe crises as a result of unanticipated changes, such as the COVID-19 pandemic, which has raised awareness of how organizations learn to become stronger. Consequently, the purpose of this study is to determine the level of learning organization (LO) of the state education official (SEO) in Malaysia from the dimensions of continuous learning, inquiry and dialogue, team and collaborative learning, embedded system, empowerment, system connection and strategic leadership as well as to explore the differences in LO practices of the SEO in Malaysia across demographic factors. Due to the COVID-19, data was collected from 450 SEOs using Google Forms. The analysis of data showed that the level of LO was very high. The different frequency of participation in courses, workshops or training related to governance, leadership or educational management during the respondent’s tenancy at the state education department (SED) was shown to be significant according to the analysis of multiple analysis of variance (MANOVA) results. However, there was no significant difference in the LO practices of SEO based on position, age, experience, and academic credentials. The finding has a significant representation of the educational management and provide a viable framework for the context of the pandemic as it can be used to compare it to findings from similar studies conducted in other regions or public sector as well as provide useful insights for countries with characteristics that are like those of Malaysia in the future.